The last word - Ribeiro, Nelson; Gorelick, Victor (Edina, Minnisota Spotlight, 2007)
The sweet girl-next-door Betty Cooper is best friends with sophisticated, gorgeous Veronica Lodge. Join the fun and see what the friends will do to win Archie.
Are you a dressing me?! -- The big countdown -- Under cover -- The last word -- The haunted beach house -- A shore thing -- Filing a compliment -- Real reality -- Seize the day -- The green horn -- Customer dis-service -- Poor fish! -- Grin and bear it!
Revision of issue 122 (Sept. 2001) of Betty and Veronica digest magazine.
9 - 11 years
Keywords: Teenagers; Graphic novels